Implementasi Algoritma K-Means dan Moora dalam Penentuan Prioritas Work Order PT Telkom Akses Divisi CCAN - Diky Wahyudi B; Mirfan, Mirfan; Syamsu Alam (Ikatan Ahli Informatika Indonesia, 2023)
PT Telkom Akses is a company engaged in the construction of development and manage service network infrastructure with every movement of the field team controlled using work orders commonly known as work orders. CCAN Assurance operations still determine priorities manually so that the risk of meeting targets is quite low. This research aims to design a system by implementing the K-MEANS and MOORA algorithms to overcome the problem of meeting the targets of each work order. The method used in this research is K-MEANS to group orders into 2 priority clusters, then MOORA will rank orders in the cluster. The K-MEANS method groups work orders into 2 priority clusters (critical links and normal links) and MOORA will rank work orders from each cluster so that the Makassar CCAN division can carry out order processing systematically where orders that enter the critical link with the highest rank become the top priority. by testing the system with division members with an assessment questionnaire, the results obtained were 87% satisfaction with the use of the new system.